2020
DOI: 10.1186/s41043-020-00219-6
|View full text |Cite
|
Sign up to set email alerts
|

Child dietary diversity and food (in)security as a potential correlate of child anthropometric indices in the context of urban food system in the cases of north-central Ethiopia

Abstract: Objective To investigate the relation of child dietary diversity and household food insecurity along with other socio-demographic with child anthropometric indices in north-central Ethiopia, an area with a high level of food insecurity and inadequate diet quality. Design A community-based cross-sectional study was used. Settings The study was conducted in Dessie and Combolcha towns of north-central Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
6
17
0
Order By: Relevance
“…Among the characteristics analysed, low income, participation in governmental income transfer programs and schooling of the head of the household were associated with MSFI. These ndings are compatible with data described by other authors [19].…”
Section: Discussionsupporting
confidence: 94%
“…Among the characteristics analysed, low income, participation in governmental income transfer programs and schooling of the head of the household were associated with MSFI. These ndings are compatible with data described by other authors [19].…”
Section: Discussionsupporting
confidence: 94%
“…These results overcome, as well, data from a recent Brazilian Report, which points to the Northern Region as the most affected by hunger in the country [10]. In the same direction, the index of severe FI found in the present study exceeds the high prevalence identified in children from Ethiopia, a country that still lives with hunger and malnutrition in urban environments [19]. Among the characteristics analyzed, a low income, participation in governmental income transfer programs and schooling of the head of the household were associated with moderate to severe food insecurity (MSFI).…”
Section: Discussionsupporting
confidence: 54%
“…The design and development of the conceptual framework for the study were guided by the literature review for factors that are associated with children's DD. 3,[7][8][9]12,13,15,[17][18][19][20][21] These cover factors related to child, maternal, household, and community characteristics that impact children's diet. The main exposure variables were wealth, household food insecurity access, mother's marital status, family size, maternal age, maternal education, maternal occupation, child sex, child age in a month, paternal education, paternal occupation, and child's place of birth order.…”
Section: Independent Variablesmentioning
confidence: 99%
“…4 DD is the potential determinant of a child’s linear growth and it has a predisposing correlation with a child’s body fat composition. 4 , 7 Poor diets, on the other hand, are a major contributor to the rising occurrence of anthropometric failures in children. 8 , 9 Consumption of a varied diet has been linked to a reduction in childhood malnutrition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation